Non-bus type perception negotiation method - HE PING; CHEN DONGNI; SONG JIAYI; SONG LONG; TENG YUE; CHEN PU (2019)
The invention discloses a non-bus type perception negotiation method, and the method comprises the steps that a first entity object and a second entity object each initialize their own device addresses and device codes; the first entity object issues a first perception request; the second entity object receives the first perception request sent by the first entity object, and the second entity object checks whether the first device address or the first device code has been locally registered or not, and performs negotiation processing according to the registration condition; the first entity object receives the second sensing request sent by the second entity object, and the first entity object checks whether the second device address or the second device code has been locally registered or not, and performs negotiation processing according to the registration condition. Through this method, other objects in the system can be perceived, and then through the negotiation with other objects to achieve the exchan